PROTOCOL: Guidance for stakeholder engagement in guideline development: A scoping review. Issue 2 (11th May 2022) - Petkovic, Jennifer; Riddle, Alison; Lytvyn, Lyubov; Khabsa, Joanne; Akl, Elie A.; Welch, Vivian; Magwood, Olivia; Atwere, Pearl; Graham, Ian D.; Grant, Sean; John, Denny; Katikireddi, Srinivasa Vittal; et al.
Abstract: This is the protocol for a Campbell systematic review. The objectives are as follows: to identify, describe, and summarize existing guidance and methods for multistakeholder engagement throughout the health guideline development process.